Soft biological shells in bioengineering - Miftahof, Roustem; Akhmadeev, Nariman R. (IOP (Series). Release 6., 2019)
Soft Biological Shells in Bioengineeringintegrates existing experimental data to construct multiscale models of various organs of the human body--the stomach, gravid uterus, urinary bladder, the small and large intestine. These models are used asin silicoplatforms to study intricate physiological and pathophysiological processes and to assess pharmacological modulations on their dynamics. This book is of value to postgraduate students, researchers and medical doctors interested in computational systems biology. Part ofSeries in Physics and Engineering in Medicine and Biology.